RSM optimization and morphological investigation of bismuth ferrite for photodegradation of organic pollutant under visible light - Farzaneh Abbasi; Mohsen Mansouri; Marjan Tanzifi (Scientific Reports)
Abstract The current study has been conducted to assess the influence of the morphology of bismuth ferrite perovskite (BiFeO3) on its photocatalytic performance. Nanorod and nanoparticle morphologies of BiFeO3 were prepared using the hydrothermal process and analyzed with several techniques. The photocatalysts’ effectiveness was appraised by MB photo-degradation in the presence of visible light. Various techniques were applied to analyze the structure, morphology, together with photoelectrochemical and optical properties of the photocatalyst. Optimum photo-degradation parameters were recognized via RSM, resulting in a maximum MB degradation efficiency of 98.2% (0.2021 min−1) in 20 min for nanorods. Whereas, the degradation yield for nanoparticles was achieved at 76% (0.075 min−1).From the radical trapping experiments, superoxide reactive radicals played a main role in MB photo-degradation. Also, BiFeO3 nanorods displayed superb stability during the five cycles of the photo-reaction procedure. This current survey suggests that the appropriate selection of nanomaterial morphology is crucial for achieving efficient photocatalysts.